Snow leopard - human conflict as a conservation challenge - a review - Moheb, Zalmai; Fuller, Todd K.; Zahler, Peter I. (Snow Leopard Reports, 2022)
Human conflict with large carnivores continues to be a great conservation challenge, and conflict with snow leopards (Panthera uncia) has been studied to understand causes and propose mitigation schemes. While the nature of snow leopard-human conflict is similar in most cases, reported studies have been case- and area-specific with mitigation strategies not necessarily based on a synthesis of relevant literature. We reviewed snow leopard literature published from 1970-2020 to identify the main drivers of human-snow leopard conflict (HSLC) and describe conservation and conflict mitigation strategies commonly employed. Based on 47 relevant peer-reviewed articles, review papers, book chapters, project reports, and other grey literature, we identified four major conflict domains: livestock management-related, socio-economic/human-related, ecological, and policy-related. Most articles suggested more than one conflict mitigation scheme. Three conflict mitigation domains – preventive, supportive, and compensatory – were widely reflected in the snow leopard-human conflict literature. The most commonly reported mitigation schemes included: 1) building or predator-proofing corrals; 2) training shepherds and improving livestock guarding; 3) livestock insurance schemes; 4) compensation for livestock predation; 5) capacity building, education, and awareness programs; and 6) improved breeding and use of guard dogs. Future management efforts need to tailor their approach depending on cultural, economic, and ecological circumstances.